Simplified regenerative procedures for intraosseous defects - Trombelli, Leonardo (Batavia, IL : Quintessence Publishing Co, Inc, 2020)
'Atlas presenting surgical and nonsurgical methods to treat intraosseous defects, with a focus on the single-flap approach, including indications and contraindications for treating defects with each method and detailed descriptions of the steps required for each procedure'--
Fundamentals in Periodontal Regeneration / Raluca Cosgarea, Dieter D. Bosshardt, Leonardo Trombelli, Anton Sculean -- Nonsurgical Treatment of Intraosseous Defects / Mario Aimetti, Giulia Maria Mariani, Federica Romano, Anna Simonelli, Leonardo Trombelli -- Simplified Surgical Regenerative Procedures : The Single-Flap Approach / Leonardo Trombelli, Roberto Farina, Anna Simonelli
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Periodontal disease; Flaps (Surgery); Periodontal Diseases -- surgery; Guided Tissue Regeneration, Periodontal -- methods; Surgical Flaps; Lambeaux (Chirurgie); Flaps (Surgery); Periodontal disease; Atlas; atlases; Atlases; Atlases; Atlas